SENAM OTAK DALAM MENINGKATKAN PERKEMBANGAN KOGNITIF ANAK USIA DINI PADA KELOMPOK B DI KOBER QURROTU’AIN AL ISTIQOMAH - Yulianti yulianti; Yanti Yanti (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2018)
Classroom learning is better if we can stimulate children according to the stage of child development. the development of the child among others is the development of moral, cognitive, language, emotional, social, motoric and artistic values. The child's cognitive development can be stimulated by the movement of brain exercises. Simple brain movement movement is identical to the movement touching certain parts of the body, so as to provide positive energies in the body of early childhood. Brain gymnastic activity is performed on the child's age because it requires an improvement in his cognitive abilities, such as completing tasks and responding to commands from his teacher. Early childhood is a child who has a very important age in improving cognitive development because of this period of time where brain development is very rapid. We carry out brain gymnastic activities aimed at improving cognitive development in Kober Qurrotu'ain Al Istiqomah.